An Analysis of Senior High School English Learning Materials: Microlearning Perspectives - Dewanti, Ratna; Sukmatanti, Rizki; Iskandar, Ifan (Indonesian EFL Journal, 2023)
AbstractMicrolearning is becoming more popular in education due to its convenience, flexibility,  and effectiveness.  The popularity emerges from the use of chunking of materials in short and understandable components  that makes it easier for learners to attain the information at their convenience. Preferably, learning materials are microlearning-designed. However, since not many teachers are well-informed about microlearning, the existing learning materials may not be microlearning-based designed. Studies focusing on this issue are relatively limited. This study aims to analyze whether English learning materials at senior high school are designed based on microlearning principles. Twenty four English learning materials covering various types of materials including textbook, e-module, webpage, as well as, pre-recorded teaching and YouTube videos designed for grade X, XI, and XII collected from three senior high schools in Jakarta were analyzed using microlearning framework. The findings of this study show that the existing learning materials do not conform to microlearning  principles. The results of this study reveals the needs to design microlearning-based materials, break the lesson units into micro contents, and produce microlearning object materials for English lessons in high schools. Key Words: microlearning, English learning materials, microlearning object materials